2018
DOI: 10.3389/fpsyg.2018.02338
|View full text |Cite
|
Sign up to set email alerts
|

The Path Is the Goal: How Transformational Leaders Enhance Followers’ Job Attitudes and Proactive Behavior

Abstract: While leading through goals is usually associated with a task-oriented leadership style, the present work links goal setting to transformational leadership. An online survey with two time points was conducted with employees to investigate the influence of transformational leadership on followers’ job satisfaction, organizational commitment, and proactive behavior via goal attributes. Findings indicate that transformational leaders influence the extent to which followers evaluate organizational goals as importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 108 publications
4
55
1
6
Order By: Relevance
“…The findings (Table 3) showed that overall, all the projects are managed using mostly the transformational leadership style (Project A = 2.86; Project B = 2.63; Project C = 2.12), followed by the transactional leadership style (Project A = 2.17; Project B = 1.87; Project C = 1.68). This finding supports past works that stipulate the preference of transformational leadership style over others for project delivery [43][44][45]. The projects scored least for a Laissez-faire amongst all the leadership styles tested.…”
Section: Leadership Styles Per Projectsupporting
confidence: 90%
“…The findings (Table 3) showed that overall, all the projects are managed using mostly the transformational leadership style (Project A = 2.86; Project B = 2.63; Project C = 2.12), followed by the transactional leadership style (Project A = 2.17; Project B = 1.87; Project C = 1.68). This finding supports past works that stipulate the preference of transformational leadership style over others for project delivery [43][44][45]. The projects scored least for a Laissez-faire amongst all the leadership styles tested.…”
Section: Leadership Styles Per Projectsupporting
confidence: 90%
“…Such a perspective is informed by what (Neal, 1997:122) calls "spirituality in management and workplace," a deeper sense of appreciating workers to extent that they are not taken as costs to be cut but worthy assets to invest in for their own personal empowerment and organisational development. Therefore transformative leaders are deeply caring as they seek to motivate and inspire their followers, given such positive work scenario, Steinmann, Klug & Maier (2018) contend that employees are more likely to achieve more than is expected.…”
Section: Transformative Leadership Notementioning
confidence: 99%
“…Although transformational leaders could activate employees' career adaptability resources, they cannot directly control their followers' adaptive behaviors. Namely, the followers have to be selfmanaged to reach their desired goals (Dust et al, 2014;Steinmann et al, 2018). In CCT, career adaptability denotes an individual's self-regulation resources which can be activated by environmental factors and direct the individual to be self-regulatory in performing adaptive behaviors (Savickas and Porfeli, 2012).…”
Section: The Mediating Role Of Career Adaptabilitymentioning
confidence: 99%
“…On the contrary, the effectiveness of TFL in enhancing employees' career adaptability is attenuated when task variety is low. In turn, employees may be less activated to deliver better task performance and to voluntarily engage in OCBO (Steinmann et al, 2018). Hence, we propose the following:…”
Section: The Moderating Role Of Task Varietymentioning
confidence: 99%